NATIONAL EXAMINATION IN PERSPECTIVE OF CRITICAL PEDAGOGY - Kerta Adhi, Made (E-Journal of Cultural Studies, 2013)
This study aims at identifying the factors contributing to why the policy on national examination is given priority, how the policy on national examination is presented in the system of educational management, its implication andrepresentation in the system of educational management applied in Senior High School in Tabanan. The critical theories such as the theory of hegemony, the theory of social practice and the theory of management in the perspective of critical pedagogy were eclectically used in the present study. Qualitative method using the approach of cultural studies was employed. The data were collected using participatory observation, in-depth interview and documentation study. The data were validated using triangulation method and descriptive-qualitative technique. The result of the study showed that the factors contributing to why the policy on national examination was given priority were educational politics and state policy, socio-cultural and global influence. The policy on national examination was represented in the school and class management by the agents within and outside school. The implication was that there was such a coalition among the agents that all the students would pass the national examination. The process of how the national examination was undertaken and the result which appeared to be good (all the students passed turned out to be hyperreality. Therefore, it was necessary to reconstruct the national education.
Keywords: national examination, educational politics, state policy, critical pedagogy.